Identification and Ranking of Core Values in Family Medicine: A Mixed Methods Study From Ukraine - Kolesnyk, Pavlo; Bayen, Sabine; Shushman, Ivanna; Kolesnyk, Andrew; Kuodza, George; Klemenc-Ketiš, Zalika; Frese, Thomas (Frontiers in Medicine, 2021)
Introduction/Context: The term core value (CV) can be defined as fundamental beliefs or principles, guiding one’s behavior in a social context. Though core competencies of family medicine (FM) have been clearly defined by WONCA, there has been an ongoing debate on what are the CV for family doctors (FDs). Ukraine is a low-income country, developing a modern European healthcare system, especially regarding FM. To implement WONCA standards, it is mandatory to assess the ongoing understanding of CV in clinical daily practice among active FDs, working in different countries of Europe including Ukraine. Research questions: How do Ukrainian FDs (Delphi group experts) define CV of FM in Ukraine and how important are these CV to Ukrainian FDs? Methods: A mixed method study was conducted in 2 steps during August and September 2020 in Ukraine. The first part was a qualitative Delphi round (n=3) design among Ukrainian FD who were familiar with teaching and terms like CV. The second part was a quantitative survey among Ukrainian FDs, who were not specially used to discuss CV. A consensus list of CV has emerged from the Delphi round study. The list was suggested to 300 FDs not involved in the Delphi team, to rank the values from 1 to 9. Demographic characteristics have been assessed for all the participants of Delphi round and quantitative survey. Results: Twenty FDs participated as experts of the first Delphi round, whereas the five experts took part in the second and the third rounds of the survey. The following six CV emerged from the Delphi round: comprehensive approach, care coordination, first recourse, continuity of care, integrated approach, patient and family centered care. The consensus list of those six CVs was then submitted to 2000 FDs picked randomly for ranking. The final sample consisted of 375 FDs (19% response rate). Discussion/conclusion: Defining CV for FM by Ukrainian FDs in a given socio-economical and historical-cultural setting is crucial to optimize primary medical care and to guarantee an appropriate and successful implementation of WONCA standards as well as CV in different countries including those where reformation of the health system is ongoing.